2007
DOI: 10.1017/s1368980007000845
|View full text |Cite
|
Sign up to set email alerts
|

Generalised and abdominal obesity and risk of diabetes, hypertension and hypertension–diabetes co-morbidity in England

Abstract: Objectives: To look at trends in generalised (body mass index (BMI) $30 kg m -2 ) and abdominal (waist circumference (WC) .102 cm in men, .88 cm in women) obesity among adults between 1993 and 2003, and to evaluate their association with diabetes, hypertension and hypertension-diabetes co-morbidity (HDC) in England. Design: Analyses of nationally representative cross-sectional population surveys, the Health Survey for England (HSE). Subjects: Non-institutionalised men and women aged $35 years. Measurements: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 23 publications
5
39
0
8
Order By: Relevance
“…In this study, we found that waist gain is associated with most MetS parameters, mainly with high levels of TGs and reduced levels of HDL-C and increased BP, as markedly observed in the literature (Carr et al, 2004;Grievink et al, 2004;Chuang et al, 2006;Menke et al, 2007;Hirani et al, 2008). On the other hand, in this study, entering FBS as a variable into analysis did not show any significant relationship with waist gain in both genders, as observed in some studies (Palaniappan et al, 2004;Stolk et al, 2005), possibly indicating a lower interference of waist gain in increases in FBS; however, some other studies showed inconsistent results (Nyamdorj et al, 2009;Sone et al, 2009).…”
supporting
confidence: 85%
“…In this study, we found that waist gain is associated with most MetS parameters, mainly with high levels of TGs and reduced levels of HDL-C and increased BP, as markedly observed in the literature (Carr et al, 2004;Grievink et al, 2004;Chuang et al, 2006;Menke et al, 2007;Hirani et al, 2008). On the other hand, in this study, entering FBS as a variable into analysis did not show any significant relationship with waist gain in both genders, as observed in some studies (Palaniappan et al, 2004;Stolk et al, 2005), possibly indicating a lower interference of waist gain in increases in FBS; however, some other studies showed inconsistent results (Nyamdorj et al, 2009;Sone et al, 2009).…”
supporting
confidence: 85%
“…The frequency of BMI Ն30 kg/m 2 is 2% to 3% in Japan and 20% to 30% in Western countries. [23][24][25][26] Because of the differences in BMI between Japanese and Western populations, values Ն25 kg/m 2 were considered elevated (in contrast to Ն30 kg/m 2 in Western populations) according to criteria of the Japan Society for the Study of Obesity. 10,26 The second criterion was elevated triglycerides (Ն150 mg/dL); the third, low high-density lipoprotein (HDL) cholesterol (Ͻ40 mg/dL in men, Ͻ50 mg/dL in women); the fourth, elevated blood pressure (systolic blood pressure Ն130 mm Hg, diastolic blood pressure Ն85 mm Hg, and/or a history of treated hypertension); and the fifth, impaired glucose tolerance (Ն110 mg/dL by the NCEP-ATP III definition, Ն100 mg/dL by the AHA/NHLBI definition, and/or a history of diabetes).…”
Section: Definition Of the Metabolic Syndromementioning
confidence: 99%
“…Obesity, defined in terms of a body mass index of 30 kg/m 2 or more, has been consistently linked to all-cause and especially cardiovascular disease mortality (Adams et al, 2006;Allison et al, 1999;Calle et al, 1999;Stevens et al, 1998). It is also associated with a range of cardiovascular and metabolic disease outcomes, such as type 2 diabetes (Ford et al, 1997;Resnick et al, 2000) and hypertension (Hirani et al, 2007;Mokdad et al, 2003), as well as overall cardiovascular disease morbidity (Bogers et al, 2007;Wilson et al, 2002). Abdominal adiposity has also been linked with psychological distress, and it has been argued that an increased vulnerability to stress in the abdominally obese may be manifest as physiological hyper-reactivity (Bjorntorp, 1991).…”
Section: Obesitymentioning
confidence: 99%